(3QSGdI aj SH GdfHj Udi Gddg Ydjg hSde hCMcGegs - (3GdQhej, MSGe GdOjf, MSjf Hf YHO GdQMef, J (B926 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdeSGFd GdeJYdbI aj HjGf CMcGe ef SH GdfHj Udi Gddg Ydjg hSde CYde Cf chf GdeYQaI JaGUjd eSGFd GdSH ef Cge GdegeGJs
(3BNQgG (B:s
(3jG Hf Efj NGQL ef ecI Edi GdeOjfI CfcQg Ydjg abGd dG JfHR HGSej aEfeG CfG fHj Gddg bGehSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdchGcH GdSGFQI (B1 / 186s
(3eYLe GdeDdajf (B1 / 614s
(3cTa GdXfhf (B1 / 871s
(3TPQGJ GdPgH (B8 / 97s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs